The gonad growth of Anguilla bicolor bicolor induced by hormone combination of HCG, MT, E2, and antidopamine - Zahri, Abdul; Sudrajat, Agus Oman; Junior, Muhammad Zairin (Indonesian Society of Scientific Aquaculture (ISSA), 2015)
ABSTRACT The aim of the study was to stimulate eel gonad growth by intramuscularly injection with a hormonal combination of human chorionic gonadotropin (hCG), methyltestosterone (T), estradiol (E2) and antidopamine (A) meanwhile 0.9% NaCl solution was used as control. Estradiol concentration in the blood serum were measured by enzyme-linked immunosorbent assay (ELISA). Stimulation with hCG 20 IU/kg in combination with MT 3 mg/kg and 10 μg/kg antidopamine (hTA treatment) very effective for increased the growth of gonads with indicators gonadosomatic index (GSI) of 4.80%, hepatosomatic index 1.01% and concentration of E2 2.49±0.67 ng/mL were significantly different (P<0.05) than others treatment after ten weeks of application. Key words: hormone, gonad growth, maturation, Indonesian short finned eel ABSTRAK Penelitian ini bertujuan untuk mengetahui pertumbuhan gonad yang distimulasi oleh kombinasi human chorionic gonadotropin (hCG), metiltestosteron (MT), estradiol (E2) dan antidopamin (A). Ikan sidat disuntik dengan hormon dan 0,9% NaCl sebagai kontrol secara intramuskular. Pengukuran konsentrasi hormon E2 dalam serum darah dengan enzyme-linked immunosorbent assay (ELISA). Stimulasi dengan hCG 20 IU/kg dikombinasi dengan MT 3 mg/kg dan antidopamin 10 μg/kg (perlakuan hTA) sangat efektif untuk feminisasi dan meningkatkan pertumbuhan gonad dengan indikator indeks gonadosomatik (GSI) 4,80%, indeks hepatosomatik 1,01% dan konsentrasi E2 2,49±0,67 ng/mL, secara signifikan berbeda pada taraf P<0,05 dibandingkan perlakuan lain setelah sepuluh minggu aplikasi. Kata kunci: hormon, pertumbuhan gonad, maturasi, sidat